Analysis on the dynamic mechanism of Acetes aggregation near a nuclear power cooling water system based on the Lagrangian flow network - Lou, Qi; Zhang, Xueqing; Xiang, Xusheng; Yu, Fan; Xiong, Ying; Li, Zhengyan (Frontiers in Marine Science, 2023)
The outbreak of nuclear power cooling-water system (NPCS) disaster-causing organisms has become more and more frequent and caused huge economic losses. It is essential to understand the aggregation mechanism of the disaster-causing organisms for the risk prevention and control of the NPCS. In this study, we apply the Lagrangian Flow Networks (LFN) to analyze the aggregation mechanism of the Acetes near NPCS as a case study. The complex network describes the interconnections between massive nodes and has been used for modelling complex nonlinear systems to reveal the mechanism of the emergence of novel processes. In this study, the degree and probability paths in the network are used to reveal the transport pathway and aggregation area of Acetes. The results show that the sea area of the nuclear power plant is the key node with a large in degree of the LFN, where the material is easy to accumulate. The Acetes near the NPCS mainly came from the east along two critical paths. Our work shows the LFN is a feasible approach to predict the transport and the accumulation of the NPCS disaster-causing plankton.